UJI AKTIVITAS ANTIBAKTERI SEDIAAN MIKROEMULSI MINYAK JINTEN HITAM (Nigella sativa L.) TERHADAP TIGA BAKTERI PENYEBAB JERAWAT - Sani Ega Priani; Tati Kurniati; Lanny Mulqie (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2020)
Black seed oil is known to contain thymoquinone and other active compounds that have antibacterial activity and potential to be developed as an anti-acne agent. The objective of this research is to develop microemulsion gel containing black seed oil and determine the antibacterial activity to three acne-causing bacteria. Black seed oil was characterized and developed to microemulsion gel preparation. Microemulsion gel was prepared using tween 80, glycerine, HPMC as surfactant, cosurfactant, and gelling agent. Microemulsion gel was evaluated including organoleptic, pH, viscosity, rheology, and stability tests. Antibacterial activity was conducted by a well diffusion method to Propionibacterium acnes, Staphylococcus epidermidis, dan Staphylococcus aureus. The result shows the formulated microemulsion gives transparent appearance and stabile. The microemulsion gel has an antibacterial activity to Propionibacterium acnes, Staphylococcus epidermidis, and Staphylococcus aureus with an average inhibitory zone 15.00 ± 1.70, 12.7 ± 0.42, 14.39 ± 0.37 mm, respectively.